SIKAP BAHASA MAHASISWA BANDUNG TERHADAP BAHASA IBU PADA ERA MILENIAL: KAJIAN SOSIOLINGUISTIK - Rani Siti Fitriani; Riva Nabila (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The millennial era changes social life, one of which is a change in student attitudes towards mother tongue. The purpose of this study is to describe how the language attitude of students in the city of Bandung towards mother tongue in the millennial era with sociolinguistic studies. The method used is descriptive method. Based on the results of data analysis, it is known that the language attitude of students in the city of Bandung towards mother tongue in the millennial era is positive and negative. The positive attitude of students is indicated by the use of Sundanese in the family environment and in the public space; students do not experience difficulties when speaking Sundanese and use speech acts; and able to sing Sundanese songs. Negative attitude towards mother tongue is seen from the number of students who cannot mention the Sundanese language wawangsalan.